Carotenoids intake and asthma prevalence in Thai children - Sanguansak Rerksuppaphol; Lakkana Rerksuppaphol (MDPI AG, 2012)
Several antioxidant nutrients have been described to inversely correlate with asthma. In order to quantify the intake of these substances, it is possible to measure skin levels by Raman spectroscopy, a novel non-invasive technique that can also be used in children. This cross-sectional school-based study involved 423 children from a rural area of Thailand. Asthmatic children were diagnosed according to a Health Interview for Asthma Control questionnaire. Skin carotenoid levels were measured with Raman spectroscopy. Demographic data were obtained by directly interviewing children and their parents, whereas anthropometric parameters were measured by trained staff. Intake of carotenoids, vitamin A and C were evaluated by a food frequency questionnaire. Overall incidence of asthma in Thai schoolchildren (aged 3.5-17.8 years) was 17.3%. There was no significant difference in dietary intake of carotenoids and vitamin A and C, and skin carotenoid level between asthmatic and nonasthmatic children. Skin carotenoid level significantly correlated with all carotenoids and vitamin A intake (P<0.05). Carotenoids and vitamin A and C intakes, and skin carotenoid levels were not associated with the risk of asthma in Thai children. Skin carotenoids correlated with all carotenoids and vitamin A intake in mild to moderate degrees. Raman spectroscopy was confirmed to be a useful tool to determine antioxidant skin levels.